Non-Protein Coding RNAs - Batey, Robert T. (Springer, 2017)
This book assembles chapters from some of the experts in Biophysics of RNA to provide a snapshot of the current status of this dynamic field. While by necessity incomplete, this book aims to survey a number of the better characterized non-protein coding RNAs and the biophysical techniques used to study them. It is written for students and researchers at all levels of accomplishment interested in understanding how non-protein coding RNAs work and how biophysical and computational approaches can be used to delineate the molecular underpinnings of RNA function. Many topics are approached with the goal of describing how biophysical tools and techniques have been used to address fundamental questions in the biology of non-protein coding RNAs, rather than a description of RNAs themselves. In this light, we hope that the book will be of particular use to junior scientists seeking to tackle new problems in RNA biology from the vantage of biophysics.